PERAN PENYULUHAN DAN EDUKASI PROGRAM BANGGA KENCANA OLEH PEMERINTAH DAERAH DALAM PENCEGAHAN STUNTING PADA ANAK DI DAERAH PEDESAAN - Nuranti, Ayu; Rahmawati, Rita; Lyndon, Novel Anak (Universitas Djuanda, 2025)
Stunting is one of the public health problems that is still a challenge in Indonesia, especially in rural areas. This condition is caused by chronic malnutrition in early life and has an impact on children's physical growth and cognitive development. The Bangga Kencana Program initiated by the government aims to increase public awareness through counseling and education in order to prevent stunting. This study aims to analyze the role of counseling and education in the Bangga Kencana Program implemented by the local government in an effort to prevent stunting in rural areas. The method used in this study is descriptive qualitative with data collection techniques through literature studies, observations, and interviews with related parties. The results of the study showed that the counseling and education provided in the Bangga Kencana Program played a significant role in increasing public understanding of the importance of balanced nutrition, exclusive breastfeeding, and appropriate parenting patterns during the First 1000 Days of Life (HPK). However, challenges such as limited counseling personnel, socio-cultural constraints, and access to information are still obstacles in the implementation of this program. Therefore, synergy is needed between local governments, health workers, and community leaders to ensure the effectiveness of the program and the sustainability of interventions in preventing stunting. With a comprehensive and community-based approach, the Bangga Kencana Program can be more optimal in improving the quality of life of children in rural areas and supporting the development of quality human resources in the future.